Utilisation of GMS lines for production ofheterotic bacterial wilt resistant hybrids in Tagetes spp. - Dr. Shilpa P; Dr. Sreelatha U; Dr. Minimol J.S.; Dr. Mini Sankar; Dr. Suma A (Journal of Horticultural Sciences, 2024)
The study was conducted using six testers, of which two (KAU M-1 and KAU M-2) were completely bacterial wilt resistant, and four genetic male sterile lines (GMS), in a line x tester model and further the F1 hybrids were evaluated in a bacterial wilt sick plot for various vegetative, floral and yield parameters along with their response to wilt incidence. Field evaluation for bacterial wilt resistance revealed that out of 24 hybrids, 13 hybrids involving KAU M-1 and KAU M-2 as testers exhibited bacterial wilt resistance. Analysis on heterosis for various characters viz., vegetative, floral, yield and total carotenoids content showed significant heterosis for many of the hybrids over mid parent, better parent and the check variety. The highest standard heterosis for yield was observed for the interspecific hybrid KU Ms-6 xx KAU M-47 (190.84%) followed by an intraspecific hybrid KAU Ms-42 x KAU M-2 (70.93%). Based on the wilt resistance and heterotic performance, these two hybrids can be suggested for commercial cultivation in wilt affected areas.
Keywords: Bacterial wilt resistance; carotenoids; heterotic hybrids; male sterile lines; Tagetes species